Mathematics Teachers’ Perceptions of The Positives of Blended Learning In Jordan - Mohammad Ali Ghunaimat; Esraa Ahmad Alawneh (Indonesian Journal of Education Research (IJoER), 2024)
Purpose of the study: The study aimed to reveal mathematics teachers’ perceptions about the positives of blended learning in Jordan. Methodology: The researcher followed a descriptive research approach, by designing the study tool (a questionnaire) to verify Mathematics teachers’ perceptions of the positives of blended learning in Jordan. Calculating frequencies and averages of mathematics teachers’ response values. Descriptive research is used in field research and helps define positives of blended learning accurately and clearly. The size of the study population was (179) teachers. And The participants of study sample members were 135 teachers. Main Findings: The findings of the study showed that mathematics teachers’ perceptions of the positives of blended learning are high, and the most prominent positives are: blended learning facilitates interpretation of mathematics curriculum content, The utilization of blended learning strategies increases student-teacher interaction, and in the teaching of mathematics, blended learning improves individual learning. Novelty/Originality of this study: Explaining the positives of blended learning from mathematics teachers’ perceptions in teaching mathematics helps mathematics teachers rely on this approach as an effective and active teaching strategy. The findings of the study also help educational decision-makers in Jordan know the positives of blended learning and thus move forward in supporting and encouraging this type of learning.